Rare earth intermetallic nitride non-spherical nano soft magnetic particle and preparation method and application thereof
The preparation of rare earth intermetallic nitride non-spherical nano-soft magnetic particles through plasma arc method solves the problem of improving the magnetic permeability and resonance frequency in the GHz frequency range of existing materials, reduces the dielectric constant, and significantly improves the high-frequency electromagnetic loss performance.
Patent Information
- Application Number
- CN202510027420.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-08
AI Technical Summary
It is difficult for existing high-frequency electromagnetic absorption materials to simultaneously increase the magnetic permeability and resonance frequency within the GHz frequency range, and the high dielectric constant leads to impedance mismatch, affecting the high-frequency absorption performance.
Rare earth intermetallic nitride non-spherical nano-soft magnetic particles are prepared by plasma arc method, and the cooling gradient is reduced by heating sleeve, the molten state is maintained and the non-spherical structure is formed, which enhances magnetocrystal anisotropy and reduces the dielectric constant.
It significantly improves the magnetic permeability and resonance frequency of nano soft magnetic particles, reduces the dielectric constant, forms a good electromagnetic matching, and significantly improves the high-frequency electromagnetic loss performance.
Smart Images

Figure CN119407184A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth-based nano soft magnetic materials, and specifically relates to a rare earth metal inter-nitride non-spherical nano soft magnetic particle, a preparation method and an application thereof. Background Art
[0002] With the rapid development of 5G communication technology and the rapid iteration of semiconductor processes, electronic components are becoming increasingly miniaturized and functionally integrated, greatly compressing the internal space of electronic devices. The problem of electromagnetic radiation interference between electronic components is becoming increasingly serious, affecting the operating stability of electronic equipment. Electromagnetic absorption materials convert electromagnetic wave energy into other forms of energy, such as heat energy, through physical mechanisms such as attenuation, thereby reducing reflection and scattering, becoming the key to solving electromagnetic interference. At present, the frequency of commercial 5G technology is concentrated in 3.4~6.0 GHz, and the operating frequency of future 6G technology is 5.9~7.1 GHz. Therefore, in order to solve the problem of high-frequency electromagnetic interference, it is urgent to develop electromagnetic absorption materials with high magnetic permeability and low dielectric constant in the high-frequency band (>5 GHz).
[0003] Initial magnetic permeability of traditional high-frequency magnetic materials μ i and resonant frequency f r The product of obeys the Snoek limit: f r ( μ i -1)=(2γ / 3)4pM S The working frequency and magnetic permeability of the material cannot be improved synchronously in the GHz frequency band, and it is gradually difficult to meet the requirements of the material at higher frequencies. The theory of magnetic moment precession bi-anisotropy points out that the easy-face magnetocrystalline anisotropic material μ i and f r The product expression is f r ( μ i -1)=0.5´γM S (H q / H j ) 0.5 , where γ, M S , H q , H j are gyromagnetic ratio, saturation magnetization, out-of-plane magnetocrystalline anisotropy field, and in-plane magnetocrystalline anisotropy field (Acta Physica Sinica, 2022, 71, 184201). Since the magnetic moment is distributed in the plane, the in-plane anisotropy is much smaller than the out-of-plane anisotropy, so a large H q / H jvalue, therefore, the easy-face magnetocrystalline anisotropic material can break through the Snoek limit and provide the product of magnetic permeability and natural resonance frequency to more than ten times or even dozens of times the original. To further improve the Snoek limit of easy-face materials, 2:17 type rare earth metal intermetallic compounds with high magnetocrystalline anisotropy can be used to achieve the requirements of dual anisotropy, thereby obtaining excellent high-frequency absorption performance. The Chinese patent literature discloses "a preparation method and application of rare earth high-frequency soft magnetic materials", with application number CN202210874052.6. The invention is to first react RCl3 with NaOH solution to obtain a rare earth metal precursor R(OH)3, add the reducing agent CaH2, mix by high-energy ball milling under argon, anneal at high temperature, wash, and dry to obtain R2Co 17 High-frequency soft magnetic material, the particle size is 4~6 μm. The Chinese patent document discloses "a kind of easy-to-surface high-frequency rare earth soft magnetic material and its preparation method", the publication number is CN118919205A. The present invention uses oil phase synthesis and reduction diffusion process to reduce Fe, Co acetylacetonate in an organic solvent into magnetic iron and cobalt nanoparticles, and then uniformly coats the surface of the magnetic particles with rare earth oxides through oil phase reaction, and finally uses calcium hydride as a reducing agent to obtain the rare earth soft magnetic material R2 (Fe x Co 1-x ) 17 , the initial value of the magnetic permeability at 2.0 GHz is 2.5~3.1, and the cutoff frequency is 4.7~8.3. Due to the low saturation magnetization intensity of 2:17 type rare earth metal intermetallic compounds, the improvement of magnetic permeability is limited.
[0004] 2:17-type rare earth metal intermetallic compounds are nitrided to form R2Fe 17 N 3-δType rare earth metal nitride, nitrogen atoms increase the Fe-Fe atomic distance, resulting in more than double the Fe-Fe exchange effect, resulting in a significant increase in saturation magnetization, further improving the soft magnetic properties of the material, and is expected to further improve the magnetic permeability and resonance frequency. The Chinese patent literature discloses "a method for preparing a 2:17 type rare earth-iron-nitrogen composite magnetic material for high frequency", patent number ZL201910213866.3, the invention uses rare earth oxides, carbonyl iron powder and / or iron oxide, and reducing agent as raw materials, through reduction diffusion reaction, and then hydrogen absorption and dehydrogenation treatment, and finally after a long period of nitrogen absorption reaction, a 2:17 type rare earth-iron-nitrogen magnetic powder is obtained, with an average particle size of 20 μm, a maximum real part of magnetic permeability of 2.6, and a dielectric constant of about 12.5. The Chinese patent document discloses "electromagnetic wave absorbing material", the publication number of which is CN101886214A. The preparation method disclosed in the invention is to first smelt an alloy containing 10-30% by weight of rare earth elements and 70-90% by weight of iron, then crush it into fine powder, and then heat it at 250-550 o C, nitrided to obtain 3-5 μm R2Fe 17 N 3-δ The micron particles prepared by the above method are much larger than the skin depth, and cannot suppress the eddy current loss in the GHz frequency range, thereby affecting the high-frequency performance of the rare earth soft magnetic material. Therefore, it is necessary to prepare nanoscale rare earth soft magnetic materials to reduce eddy current loss.
[0005] Rare earth elements have extremely rich electronic energy levels, 1-3 orders of magnitude more than the number of electronic energy level transitions of other elements in the periodic table, which makes rare earth metals active and can react with almost all elements. They easily lose electrons to form compounds with multiple valence states and multiple coordination numbers. Therefore, it is difficult to prepare nano-scale rare earth intermetallic compound particles by traditional wet chemical methods, ultrasonic crushing methods, mechanical ball milling methods, etc. The DC arc plasma method is a method of converting metal materials into nanoparticles by arc discharge. This method utilizes the high-temperature plasma and arc gas dynamic effects generated during arc discharge, so that the metal materials in the arc evaporate, gasify and ionize, collide in the high-temperature arc zone, and form nano-sized clusters. The surface tension causes the molten clusters to automatically shrink into spheres to minimize the surface energy. Subsequently, the nanoparticles sputter out of the arc zone and solidify into spherical nanoparticles through rapid cooling (Journal of Materials Science, 2019, 33, 1089-1098). The Chinese patent document discloses "a rare earth metal compound nano soft magnetic particle and its preparation method and application", with patent number ZL202111360424.5. This invention prepares R2M by direct current arc plasma method. 17The nanoparticles are spherical intermetallic compounds with uniform morphology and a particle size of 20-200 nm. Their natural resonance frequency is in the high frequency range (>4 GHz), but their magnetic permeability is only 1.5-2.1, while their dielectric constant is 5-7. Compared with micron particles, although the dielectric constant of nano-spherical particles is significantly reduced, it is still far from the magnetic permeability, resulting in impedance mismatch and affecting high-frequency absorption performance. Based on its working principle, the nanoparticles prepared by the traditional DC arc plasma method are spherical. The morphology of nanomaterials is one of the important factors affecting the intrinsic properties. The periodicity and density of the atomic arrangement of the crystal along different directions of the lattice are different, resulting in different properties of the crystal in different directions. Spherical particles have a smooth surface and relatively uniform polarization, and have a higher dielectric constant. Non-spherical particles have a relatively low dielectric constant due to their uneven surface and low polarization efficiency (Chemistry of Materials 2010, 22,1567-1578). At the same time, different faces of magnetic nanoparticles present different spin distributions, generating anisotropic fields and further enhancing the resonant frequency. Therefore, it is urgent to develop rare earth metal nitride non-spherical nanoparticles to reduce the dielectric constant and enhance the magnetic permeability and resonant frequency, and further improve the high-frequency electromagnetic loss performance. Summary of the invention
[0006] In order to make up for the shortcomings of the prior art, the present invention provides a rare earth metal nitride non-spherical nano soft magnetic particle and a preparation method thereof. The rare earth metal nitride nanoparticle integrates strong easy surface anisotropy and shape anisotropy, obtains greater magnetocrystalline anisotropy, and further improves the resonance frequency and magnetic permeability in the high frequency range (>5 GHz). At the same time, the non-spherical nanostructure reduces the dielectric constant and suppresses eddy current loss, which is conducive to forming a good impedance matching. Its high-frequency electromagnetic absorption performance far exceeds that of rare earth metal compound micron materials and rare earth metal compound spherical nanoparticles.
[0007] In order to achieve the above requirements, the technical solution adopted by the present invention is: A method for preparing non-spherical nano-sized soft magnetic particles of rare earth metal nitrides, wherein the atomic expression of the non-spherical nano-sized soft magnetic particles of rare earth metal nitrides is R2Fe 17 N 3-δ , wherein R represents a rare earth element, which is one or a combination of Y, La, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Lu elements, wherein the range of δ is 0-0.8, characterized in that it comprises the following steps: Step (1): Obtain a metallic target material, wherein the target material is any one of the following two types: The first method is to mix Fe and rare earth metal R to make a metallic target. The second type: R2Fe17 A target material composed of a rare earth compound alloy; Step (2): placing the target material in a plasma arc furnace as an anode, evacuating the furnace, and then filling it with ammonia; Step (3): energizing the plasma arc furnace, adjusting the distance between the cathode and the target material to form a stable plasma arc, and using the stable plasma arc to process the target material to prepare molten nano-metal clusters; Step (4): construct a tubular heating sleeve to enclose the cathode, anode and part of the arc edge area of the plasma arc in the heating sleeve; keep the inner surface of the heating sleeve constant at a preset temperature, and use the heating effect of the heating sleeve to reduce the cooling gradient inside and outside the plasma arc column, so that the nanoclusters remain in a molten state in a larger spatial range and further collide and grow, thereby weakening the surface tension effect and maintaining the lattice growth habit, and obtaining non-spherical nanoparticles; if the heating sleeve is not used, according to the traditional arc furnace process, because the nanoparticles cannot remain in a molten state in a larger spatial range, it is not conducive to further collision and growth. In the case of a very small volume, the surface tension effect is obvious. Under the action of surface tension, only spherical products can be generated. The present invention uses a heating sleeve to surround the arc area for generating molten nanometal clusters, and heats the peripheral areas such as the arc edge area, thereby reducing the cooling gradient, so that the molten nanometal clusters can continue to grow in the arc edge area and the more peripheral areas that were originally low temperature areas. group The dual strategy of cluster growth and reduced cooling gradient weakens the effect of surface tension on the spheroidization of nanoparticles, allowing the nanoparticles to maintain a non-spherical structure.
[0008] Step (5): After cooling the nanoparticles, a passivation gas is introduced into the plasma arc furnace to obtain rare earth metal internitride non-spherical nano soft magnetic particles.
[0009] Preferably, the Fe is mixed with a rare earth metal R in a mixing ratio of: rare earth metal R: 20 at%-50 at%, Fe: 50 at%-80 at%.
[0010] Preferably, in step (2), the vacuum degree of the vacuum pumping is 1.0´10 -2 Pa below; the filling of ammonia includes maintaining the pressure in the plasma arc furnace at 1.0´10 3 ~1.0´10 5 Pa.
[0011] Preferably, in step (3), the distance between the cathode and the target is 3-10 mm, the voltage range of the power supply is 20-200 V, and the current range is 50-500 A.
[0012] Preferably, in step (3), the cathode is a high melting point material, including any one of graphite, tungsten and niobium.
[0013] Preferably, in step (4), the inner diameter of the heating jacket is 3 to 5 times the diameter of the plasma arc column, so that part of the arc edge area is surrounded by the heating jacket; the height of the heating jacket is 1.5 to 2 times the height of the plasma arc column, so that the temperature-stable area in the middle of the heating jacket is directly opposite to the cathode and anode, and the inner surface temperature of the heating jacket is 400 to 1000 o C.
[0014] Preferably, in step (5), the cooling temperature is 0 o C~ 20 o C.
[0015] Preferably, in step (5), the passivation gas is oxygen or air.
[0016] The present invention also provides a rare earth metal nitride non-spherical nano soft magnetic particle prepared by the preparation method, wherein the nano particle has a polyhedral structure and a particle size range of 100-600 nm.
[0017] The rare earth metal nitride non-spherical nanometer soft magnetic particles provided by the invention are applied to GHz electromagnetic absorption. The rare earth metal nitride non-spherical nanometer soft magnetic particles are mixed with paraffin and then molded to perform GHz electromagnetic absorption.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1) Compared with spherical nano-soft magnetic particles, rare earth metal internitride non-spherical nano-soft magnetic particles have high saturation magnetization intensity, strong easy face anisotropy and large shape anisotropy, which is conducive to further improving the natural resonance frequency and magnetic permeability in the high frequency range (>5 GHz).
[0019] 2) The non-spherical nano-soft magnetic particles of rare earth metal nitrides have greater resistance, reduce the dielectric constant, and are conducive to forming good electromagnetic matching. At the same time, they can inhibit the skin effect, reduce eddy current loss, and obtain excellent high-frequency electromagnetic loss performance.
[0020] 3) The rare earth metal nitride nano soft magnetic particles prepared by the present invention are non-spherical and have a particle size of 100-600 nm. The process is simple, environmentally friendly, and has a large output, making it suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of plasma arc furnace structure and arc zone Figure 2 is the X-ray diffraction pattern of the material in Example 1; Figure 3 is a transmission electron microscope image of the material in Example 1; Figure 4 is a graph showing the relationship between the magnetic permeability and frequency of the material in Example 1; Figure 5 is a graph showing the relationship between the dielectric constant and frequency of the material in Example 1; Figure 6 This is a graph showing the electromagnetic absorption performance of the material in Example 1; Figure 7 is the X-ray diffraction pattern of the material in Example 2; Figure 8 is a transmission electron microscope image of the material in Example 2; Fig. 9 is a graph showing the relationship between the magnetic permeability and frequency of the material in Example 2; Fig.10 is a graph showing the relationship between the dielectric constant and frequency of the material in Example 2; Fig.11 This is a graph showing the electromagnetic absorption performance of the material in Example 2; Fig.12 is the X-ray diffraction pattern of the material in Example 3; Fig.13 is a transmission electron microscope image of the material in Example 3; Fig.14 is a graph showing the relationship between the magnetic permeability and frequency of the material in Example 3; Fig.15 is a graph showing the relationship between the dielectric constant and frequency of the material in Example 3; Fig.16 This is a graph showing the electromagnetic absorption performance of the material in Example 3; DETAILED DESCRIPTION
[0022] The technical scheme, process steps and features of the present invention are further described in detail below with reference to the accompanying drawings and specific examples.
[0023] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0024] The heating zone in the present invention specifically refers to a tubular heating jacket constructed near the nanocluster generation zone, which surrounds the cathode, anode and arc edge in the heating jacket, and the area surrounded by the inner wall of the heating jacket is the heating zone.
[0025] The rare earth metal internitride non-spherical nano soft magnetic particles and paraffin are mixed in a mass ratio of 1:1 and then compression molded to obtain a coaxial ring sample, which is used to perform a GHz electromagnetic absorption performance test. Example
[0026] 20 at% Ce and 80 at% Fe were uniformly mixed to prepare a target material, which was placed in a plasma arc furnace as an anode and evacuated to 1.0´10 -2 Pa, fill with ammonia to keep the pressure of plasma arc furnace at 1.0´10 3 Pa. Turn on the power supply, control the voltage to 20 V, the current to 50 A, adjust the distance between the tungsten cathode and the target to 3 mm, form a stable arc, and prepare the target into molten nanometal clusters. The diameter of the heating zone is 3 times the diameter of the plasma arc column, the height is 1.5 times the height of the plasma arc column, and the temperature is 400 o C. Introduce circulating water at 0 o The product is cooled under C conditions, and then oxygen is introduced as a passivation gas to obtain rare earth metal internitride non-spherical nano soft magnetic particles.
[0027] The X-ray diffraction pattern of the obtained rare earth metal nitride nano soft magnetic particles is as follows: Figure 2 As shown by Figure 2 The diffraction peak in the middle can be used to determine that the material is Ce2Fe 17 N 3-δ Its microscopic appearance is as follows Figure 3 As shown in the figure, it can be seen that the particles are non-spherical in structure and the particle size is about 100-300 nanometers. The relationship between magnetic permeability and frequency is as follows Figure 4 As shown, it can be seen that the resonant frequency is 7.04 GHz and the maximum value of the real part of the magnetic permeability is 3.73. The relationship between the dielectric constant and the frequency is as follows Figure 5 As shown, it can be seen that the real part of the dielectric constant is between 4.11 and 4.92. The electromagnetic absorption performance is shown in Figure 6 As shown, it has strong absorption (-51.1 dB) and a wide absorption band (10.45 GHz) at GHz frequency. Example
[0028] 50 at% Pr and 50 at% Fe were uniformly mixed to prepare a target material, and the target material was placed in a plasma arc furnace as an anode and evacuated to 1.0´10 -2 Pa, fill with ammonia to keep the pressure of plasma arc furnace at 1.0´10 5 Pa. The power supply was turned on, the voltage was controlled to be maintained at 200 V, the current was maintained at 500 A, and the distance between the tungsten cathode and the target was adjusted to be maintained at 10 mm to form a stable arc, and the target was prepared into molten nanometal clusters. A heating zone was applied near the nanocluster generation area, the diameter of the heating zone was 5 times the diameter of the plasma arc column, the height was 2 times the height of the plasma arc column, and the temperature was 1000 o C. The circulating water is at 20 oThe product is cooled under C conditions and then filled with oxygen to obtain rare earth metal internitride non-spherical nano soft magnetic particles.
[0029] The X-ray diffraction pattern of the obtained rare earth metal nitride nano soft magnetic particles is as follows: Figure 7 As shown by Figure 7 The diffraction peak in the middle can be used to determine that the material is Pr2Fe 17 N 3-δ Its microscopic appearance is as follows Figure 8 As shown in the figure, it can be seen that the particles are non-spherical in structure and the particle size is about 100-600 nanometers. The relationship between magnetic permeability and frequency is as follows Fig. 9 As shown, it can be seen that the resonant frequency is 9.63 GHz and the maximum value of the real part of the magnetic permeability is 3.64. The relationship between the dielectric constant and the frequency is as follows Fig.10 As shown, it can be seen that the real part of the dielectric constant is between 3.07 and 4.64. The electromagnetic absorption performance is shown in Fig.11 As shown, it has strong absorption (-27.3 dB) and a wide absorption band (13.27 GHz) at GHz frequency. Example
[0030] Y2Fe 17 The rare earth compound is used as the target material, and the target material is placed in a plasma arc furnace as an anode and evacuated to 1.0´10 -2 Pa, fill with ammonia to keep the pressure of plasma arc furnace at 1.0´10 4 Pa. The power supply was turned on, the voltage was controlled to be maintained at 100 V, the current was maintained at 100 A, and the distance between the tungsten cathode and the target was adjusted to be maintained at 5 mm to form a stable arc, and the target was prepared into molten nanometal clusters. A heating zone was applied near the nanocluster generation area, the diameter of the heating zone was 4 times the diameter of the plasma arc column, the height was 1.8 times the height of the plasma arc column, and the temperature was 600 o C. The circulating water is introduced at 10 o The product is cooled under C conditions and then filled with air to obtain rare earth metal internitride non-spherical nano soft magnetic particles.
[0031] The X-ray diffraction pattern of the obtained rare earth metal nitride nano soft magnetic particles is as follows: Fig.12 As shown by Fig.12 The diffraction peak in the middle can be used to determine that the material is Y2Fe 17 N 3-δ Its microscopic appearance is as follows Fig.13 As shown, it can be seen that the particles are non-spherical and the particle size is about 100-400 nanometers. The relationship between magnetic permeability and frequency is as follows Fig.14 As shown, it can be seen that the resonant frequency is 8.2 GHz and the maximum value of the real part of the magnetic permeability is 3.48. The relationship between the dielectric constant and the frequency is as follows Fig.15 As shown, it can be seen that the real part of the dielectric constant is between 4.05 and 5.15. The electromagnetic absorption performance is shown in Fig.16 As shown, it has strong absorption (-52.87 dB) and a wide absorption band (13.11 GHz) at GHz frequency.
Claims
1. A method for preparing non-spherical nano-sized soft magnetic particles of rare earth metal nitrides, wherein the atomic expression of the non-spherical nano-sized soft magnetic particles of rare earth metal nitrides is R2Fe 17 N 3-δ , wherein R represents a rare earth element, which is one or a combination of Y, La, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Lu elements, wherein the range of δ is 0~0.8, characterized in that, The steps include: Step (1): Obtain a metallic target material, wherein the target material is any one of the following two types: The first method is to mix Fe and rare earth metal R to make a metallic target. The second type: R2Fe 17 A target material composed of a rare earth compound alloy; Step (2): placing the target material in a plasma arc furnace as an anode, evacuating the furnace, and then filling it with ammonia; Step (3): energizing the plasma arc furnace, adjusting the distance between the cathode and the target material to form a stable plasma arc, and using the stable plasma arc to process the target material to prepare molten nano-metal clusters; Step (4): constructing a tubular heating jacket to enclose the cathode, the anode and a portion of the arc edge area of the plasma arc in the heating jacket; The inner surface of the heating jacket is kept constant at a preset temperature, and the heating effect of the heating jacket is used to reduce the cooling gradient inside and outside the plasma arc column, so that the nanoclusters remain in a molten state in a larger space range, further collide and grow, thereby weakening the surface tension effect and maintaining the lattice growth habit, and obtaining non-spherical nanoparticles; Step (5): After cooling the nanoparticles, a passivation gas is introduced into the plasma arc furnace to obtain rare earth metal internitride non-spherical nano soft magnetic particles.
2. The method for preparing the rare earth metal nitride non-spherical nano soft magnetic particles according to claim 1, characterized in that: In step (1), the Fe is mixed with a rare earth metal R, and the mixing ratio is: rare earth metal R: 20 at%-50 at%, Fe: 50 at%-80 at%.
3. The method for preparing the rare earth metal nitride non-spherical nano soft magnetic particles according to claim 1, characterized in that: In step (2), the vacuum degree of the vacuum pump is 1.0´10 -2 Pa below; the filling of ammonia includes maintaining the pressure in the plasma arc furnace at 1.0´10 3 ~1.0´10 5 Pa.
4. The method for preparing the rare earth metal nitride non-spherical nano soft magnetic particles according to claim 1, characterized in that: In step (3), the distance between the cathode and the target is 3-10 mm, the voltage range of the power supply is 20-200 V, and the current range is 50-500 A.
5. The method for preparing the rare earth metal nitride non-spherical nano soft magnetic particles according to claim 1, characterized in that: In step (3), the cathode is made of a high melting point material, including any one of graphite, tungsten and niobium.
6. The method for preparing the rare earth metal nitride non-spherical nano soft magnetic particles according to claim 1, characterized in that: In step (4), the inner diameter of the heating jacket is 3 to 5 times the diameter of the plasma arc column, the height of the heating jacket is 1.5 to 2 times the height of the plasma arc column, and the inner surface temperature of the heating jacket is 400 to 1000 o C.
7. The method for preparing the rare earth metal nitride non-spherical nano soft magnetic particles according to claim 1, characterized in that: In step (5), the cooling temperature is 0 o C~ 20 o C.
8. The method for preparing the rare earth metal nitride non-spherical nano soft magnetic particles according to claim 1, characterized in that: In step (5), the passivation gas is oxygen or air.
9. A rare earth metal nitride non-spherical nano soft magnetic particle prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The nanoparticles are polyhedral in structure and have a particle size range of 100-600 nm.
10. The rare earth metal inter-nitride non-spherical nano soft magnetic particles according to claim 9 are applied to GHz electromagnetic absorption, characterized in that: The rare earth metal internitride non-spherical nano soft magnetic particles are mixed with paraffin wax and then molded to perform GHz electromagnetic absorption.
Citation Information
Patent Citations
Electromagnetic wave absorbing material
CN101886214A
Preparation method of 2:17 type rare earth-iron-nitrogen composite magnetic material for high frequency use
CN110047637A
Preparation method and application of rare earth high-frequency soft magnetic material
CN115623766A
Easily-planar high-frequency rare earth soft magnetic material and preparation method thereof
CN118919205A
Fe nanometer dot @ BN nanospherecompound and preparation method and application thereof
CN108746598A